Long noncoding RNA Gm4419 promotes mesangial cell proliferation and extracellular matrix accumulation via the miR-455-3p/histone deacetylase 2 axis - Yang Wen; Hua Gan; Qing Zhong; Ying Gong (Heliyon)
Long noncoding RNAs may function as competitive endogenous RNAs by sponging microRNAs, thereby contributing to the progression of diabetic nephropathy. In this study, a potential diabetic nephropathy-related long noncoding-microRNA-mRNA axis, Gm4419-miR-455-3p-Hdac2, was predicted using bioinformatics methods. To verify the role of the Gm4419-miR-455-3p-Hdac2 axis in diabetic nephropathy, an in vitro high glucose-induced mesangial cell model was established. The expression levels of Gm4419, miR-455-3p and Hdac2 were detected using reverse-transcription quantitative PCR. Protein levels of collagen IV, fibronectin and transforming growth factor-beta 1 were detected using western blotting. Cell counting kit-8 assay and 5-ethynyl-2′-deoxyuridine staining assay were adopted to assess cell proliferation. Cell transfection, fluorescence in situ hybridization, RNA immunoprecipitation, and dual luciferase reporter assay were also performed. Our results revealed significant cell proliferation and extracellular matrix accumulation in high glucose-treated mesangial cells. In addition, Gm4419 and Hdac2 levels were increased and miR-455-3p was decreased in high glucose-treated mesangial cells. The interaction between Gm4419 and miR-455-3p or miR-455-3p and Hdac2 was confirmed by reverse-transcription quantitative PCR and dual luciferase reporter assay. Gene silencing of Gm4419 inhibited mesangial cells proliferation and extracellular matrix accumulation. MiR-455-3p inhibitor counteracted the effects of Gm4419 gene silencing on cell proliferation and extracellular matrix accumulation, which was reversed again by Hdac2 gene silencing. In summary, our research indicates that gene silencing of Gm4419 can effectively inhibit high glucose-induced mesangial cells proliferation and extracellular matrix accumulation. This is achieved through the regulation of the miR-455-3p/Hdac2 axis, highlighting the potential of the Gm4419-miR-455-3p-Hdac2 axis as a promising therapeutic target for the treatment of diabetic nephropathy.